Care home manager attitudes to balancing risk and autonomy for residents with dementia. (1st February 2018) - Evans, Elizabeth A; Perkins, Elizabeth; Clarke, Pam; Haines, Alina; Baldwin, Ashley; Whittington, Richard
ABSTRACT: Objective: To determine how care home managers negotiate the conflict between maintaining a safe environment while enabling the autonomy of residents with dementia. This is important because there is limited research with care home managers; yet, they are key agents in the implementation of national policies. Method: Semi-structured interviews were conducted with 18 managers from care homes offering dementia care in the Northwest of England. Data were analysed using a thematic analysis approach. Results: There were three areas in which care home staff reported balancing safety and risk against the individual needs of residents. First, the physical environment created a tension between safety and accessibility to the outside world, which meant that care homes provided highly structured or limited access to outdoor space. Second, care home managers reflected a balancing act between an individual's autonomy and the need to protect their residents' dignity. Finally, care home managers highlighted the ways in which an individual's needs were framed by the needs of other residents to the extent that on some occasions an individual's needs were subjugated to the needs of the general population of a home. Conclusion: There was a strong, even dominant, ethos of risk management and keeping people safe. Managing individual needs while maintaining a safe care home environment clearly is a constant dynamic interpersonal process of negotiating and balancing competing interests for care home managers.